Experimental studies on precast concrete beam‐column connections with precast irregularly shaped columns and composite beams subjected to cyclic loading. (15th October 2021) - Hu, Xiang; Xue, Weichen; Zhang, Li
Abstract: In this article, the precast concrete beam‐column connections, composed of precast irregularly shaped columns, composite beams and cast‐in‐place (CIP) core regions, were designed as emulative connections. In order to investigate the seismic behaviors of the precast connections, four full‐scale specimens, including an interior and an exterior precast specimen and their CIP control specimens, were tested under cyclic loading. The results revealed that the failure pattern of the precast specimens was characterized by flexural failure at the beam ends near the column face, which were similar to the CIP control specimens. Meanwhile, the concrete of core regions near the bottom of the beams slightly spalled, and diagonal cracks appeared in the core regions. The hysteresis loops of all the specimens were relatively plump, showing good energy dissipation capacity. The precast specimens exhibited slightly stronger response than the CIP control specimens, as the load carrying capacity of the precast interior and exterior specimens were about 2% and 5% higher, respectively. All the precast and CIP specimens behaved in a relatively ductile manner. The ductility of the interior and exterior precast specimens was 2.8 and 2.7, which was approximate to that of the CIP control specimens. The stiffness degradation of the precast specimens was also found to be similar to that of the CIP control specimens. Finally, a degenerated four‐linear restoring force model was developed.